Peran Sekuens Genom Mitokondria dan Susunan Gen Sarcoptes Scabiei terhadap Karakterisasi Genetik Pasien Terinfestasi Skabies - Trasia, Reqgi First; Mustofa, Samsul; Purwaningsih, Endang; Herlinawati, Sri Wahyu (Penerbit Goodwood, 2024)
Purpose: The aim of writing this article is to examine the draft genome of S. scabiei from a number of published articles Research methodology: This article reviews scabies genome sequencing, which may provide the necessary facilities to investigate the many unknowns associated with the survival of scabies mites. Results: Scabies genome sequencing investigated many unknowns related to scabies mite survival, reproduction, and host-parasite interactions and may facilitate studies in the areas of developing scabies diagnostic tests, new treatments, and vaccines to protect against this disease. Limitations: From the results of sequencing, assembly, and annotation of the scabies mite mitochondrial genome, the experts identified SNPs in several isolates from patients and laboratory pig models and inferred the haplotype structure and diversity of individual infections. Contribution: The results of multi-locus studies in a number of countries indicate that different varieties of Sarcoptes mites originate from different host species and geographic regions and recommend a common gene pool of S. scabiei that represents the existence of a single species.